2018
DOI: 10.1186/s13068-018-1266-x
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of a single glycosyltransferase in Caldicellulosiruptor bescii eliminates protein glycosylation and growth on crystalline cellulose

Abstract: Protein glycosylation pathways have been identified in a variety of bacteria and are best understood in pathogens and commensals in which the glycosylation targets are cell surface proteins, such as S layers, pili, and flagella. In contrast, very little is known about the glycosylation of bacterial enzymes, especially those secreted by cellulolytic bacteria. Caldicellulosiruptor bescii secretes several unique synergistic multifunctional biomass-degrading enzymes, notably cellulase A which is largely responsibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…Glycosylation of CelA with galactose disaccharides was confirmed by overexpression in the C. bescii ∆celA strain [89,90], only extracellular CelA was observed as being glycosylated [89] and the glycotransferase (GT) located in the GDL is required for CelA glycosylation [79,91]. Initially, deletion of the GT responsible for glycosylation of CelA resulted in proteolytic clipping of extracellular enzymes and lower cell densities observed by plate counts from planktonic cells growing on microcrystalline cellulose [91]. In contrast, deletion of the same GT from a different parental C. bescii strain did not result in a dramatic effect, and the GT deletion strain was still capable of solubilizing microcrystalline cellulose [79].…”
Section: Celamentioning
confidence: 97%
See 3 more Smart Citations
“…Glycosylation of CelA with galactose disaccharides was confirmed by overexpression in the C. bescii ∆celA strain [89,90], only extracellular CelA was observed as being glycosylated [89] and the glycotransferase (GT) located in the GDL is required for CelA glycosylation [79,91]. Initially, deletion of the GT responsible for glycosylation of CelA resulted in proteolytic clipping of extracellular enzymes and lower cell densities observed by plate counts from planktonic cells growing on microcrystalline cellulose [91]. In contrast, deletion of the same GT from a different parental C. bescii strain did not result in a dramatic effect, and the GT deletion strain was still capable of solubilizing microcrystalline cellulose [79].…”
Section: Celamentioning
confidence: 97%
“…In contrast, Conway et al monitored cellulose solubilization in vivo, and other factors aside from glycosylation may impact enzyme efficiency [79]. Lastly, while fewer C. bescii GT knock out colonies were observed by Russell et al, [91], no comparison in growth on a solid medium was made between planktonic cells grown on cellobiose versus cellulose. It is possible that in addition to reduced stability of extracellular hydrolytic enzymes, the glycosylation deficient C. bescii strains are also deficient in their ability to form colonies on solid medium, resulting in a false negative result for growth on microcrystalline cellulose.…”
Section: Celamentioning
confidence: 98%
See 2 more Smart Citations
“…As we were unable to assay the activity of CkGE15A at elevated temperatures due to the temperature sensitivity of the substrates, this comparison is likely not a good reflection of the enzyme's true catalytic efficiency at high temperatures. Additionally, Caldicellulosiruptor bacteria have been shown to glycosylate CAZymes [59,60], and possibly also CkXyn10C-GE15A is glycosylated in vivo and requires these post-translational modifications for full activity, as it has previously been shown that glycosylation is of great importance to the activity of other esterases, increasing their reaction rates by several orders of magnitude [61]. All of these factors considered, it is likely that the true kinetic parameters for CkGE15A is significantly higher than reported here.…”
Section: Determination Of Glucuronoyl Esterase Activitymentioning
confidence: 60%